Effect of wheat bran derived prebiotic supplementation on gastrointestinal transit, gut microbiota, and metabolic health: a randomized controlled trial in healthy adults with a slow gut transit. Issue 1 (9th November 2020) - Müller, Mattea; Hermes, Gerben D. A.; Emanuel E., Canfora; Holst, Jens J.; Zoetendal, Erwin G.; Smidt, Hauke; Troost, Freddy; Schaap, Frank G.; Damink, Steven Olde; Jocken, Johan W. E.; Lenaerts, Kaatje; Masclee, Ad A. M.; et al.
ABSTRACT: Acute intake of the wheat bran extract Arabinoxylan-Oligosaccharide (AXOS) modulates the gut microbiota, improves stool characteristics and postprandial glycemia in healthy humans. Yet, little is known on how long-term AXOS intake influences gastrointestinal (GI) functioning, gut microbiota, and metabolic health. In this randomized, placebo-controlled, double-blind study, we evaluated the effects of AXOS intake on GI function and metabolic health in adults with slow GI transit without constipation. Forty-eight normoglycemic adults were included with whole-gut transit time (WGTT) of >35 h receiving either 15 g/day AXOS or placebo (maltodextrin) for 12-wks. The primary outcome was WGTT, and secondary outcomes included stool parameters, gut permeability, short-chain fatty acids (SCFA), microbiota composition, energy expenditure, substrate oxidation, glucose, insulin, lipids, gut hormones, and adipose tissue (AT) function. WGTT was unchanged, but stool consistency softened after AXOS. 12-wks of AXOS intake significantly changed the microbiota by increasing Bifidobacterium and decreasing microbial alpha-diversity. With a good classification accuracy, overall microbiota composition classified responders with decreased WGTT after AXOS. The incretin hormone Glucagon-like protein 1 was reduced after AXOS compared to placebo. Energy expenditure, plasma metabolites, AT parameters, SCFA, and gut permeability were unchanged. In conclusion, intake of wheat bran extract increases fecal Bifidobacterium and softens stool consistency without major effects on energy metabolism in healthy humans with a slow GI transit. We show that overall gut microbiota classified responders with decreased WGTT after AXOS highlighting that GI transit and change thereof were associated with gut microbiota independent of Bifidobacterium . NCT02491125